Leadership and Emotional Intelligence: Current Trends in Public Health Professionals Training - Reshetnikov, Vladimir A.; Tvorogova, Nadezhda D.; Hersonskiy, Ilya I.; Sokolov, Nikita A.; Petrunin, Alexander D.; Drobyshev, Dmitriy A. (Frontiers in Public Health, 2020)
Aim of the study:To identify and compare the most significant personal features, social,psychophysiological characteristics of future healthcare managers in order to improve the training program for specialists in the field of healthcare and public health, based on modern conceptions about the necessary leadership skills and competences.Significance:The results of the study make it possible to evaluate the effectiveness of career guidance and selection for training future health care managers based on the application of the following methods: the assessment of emotional intelligence and taking into account the psychological characteristics of students.Materials and methods:242 students studying medical and preventive care, residents,as well as undergraduate students who were trained in the program"Factory of Health Leaders"were included in the study evaluating the level of professional training and indicators of emotional intelligence. Participants underwent testing using methodology of the management style assessment, as well as testing showing the psychophysiological and emotional characteristics of respondents.Results:Students who studied in the “FactoryofHealthLeaders”program had better indicators of emotional intelligence than ordinary students, but their rates are comparable to residents’ rates. This makes us understand that the additional training of emotional intelligence in the process of studying under the higher education program can be successful along with great practical experience in healthcare as among residents’ curriculum. Conclusion:The training of leadership qualities and emotional intelligence in students using the example of comparing students in the“Factory of Health Leaders”program with students who have not undergone such training,has confirmed its high efficiency and significance in the training of highly qualified personnel in healthcare.